تقرير التجارة والتنمي ة 2022 - United Nations Conference on Trade; Development (United Nations, 2023)
The Trade and Development Report 2022 analyses current economic trends and major policy issues of international concern, and makes suggestions for addressing these issues at various levels. This year report emphasizes that structural imbalances and inequalities in the global macroeconomic environment have grown since the global financial crisis and have intensified further with the Covid-19 pandemic. With less than a decade to meet the Agenda 2030, the Trade and Development Report 2022 finds that current policy trends could imperil the progress of developing countries towards inclusive and sustainable development. While improved policy coordination is needed at the multilateral level to better address the vulnerabilities facing developing countries, scaling up and strengthening regional arrangements can also help widen the opportunities from closer economic integration.